Goal commitment is in the eye of the beholder: Causes and consequences of perceiving others' goal commitment. Issue 6 (2nd November 2021) - Curtis, Jessica; Burkley, Edward; Hatvany, Thomas; Higdon, Brandon J.
ABSTRACT: The present work examines how judgments of others' commitment to a goal are influenced by three factors that influence one's own goal commitment (satisfaction, investment, and alternatives). In two studies these three factors were manipulated. The results indicated that people rate another's goal commitment higher when goal satisfaction is high, goal investment is high and goal alternatives are low. It was also found that satisfaction and investments alter perceptions of the other's abilities, and that this relationship is partially mediated by perceived goal commitment. The present studies offer novel findings that highlight the information we use to judge the goal commitment of others and the consequences that are incurred when these judgments are formed.